Latihan Sepakbola Untuk Mengembangkan Bakat Anak Anak di Desa Teluk Merbau - Agus Sulastio; Ardi Samawi; Aina Riskia; Alya Amanda; Bifanda Ariandana; Vicky Tigris; Ahmadia Zahroi; Azhari Lubis; Deswita Adriani; Muhamad Alfajar; Muhammad Farras Fadlurrahman (Lembaga Pengembangan Kinerja Dosen, 2024)
Football is a team sport played by two teams, each consisting of eleven players, on a rectangular field with goals at each end. The aim of this game is to score a goal by putting the ball into the opponent's goal and preventing the opponent from scoring a goal into their own team's goal. The game takes place in two halves of 45 minutes each, with a break between halves. The team that scores the most goals at the end of the match is declared the winner. If the score is level, the match may go to extra time or a penalty shootout, depending on the competition format. Football is also known by various special terms and rules, such as offside, corner kicks, and yellow/red cards. In addition, football is a very popular sport throughout the world and is often held in various competitions, including domestic leagues and international tournaments such as the FIFA World Cup.